ETIKA DAN TANGGUNG JAWAB HUKUM AUDITOR - Budi Gautama (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
Ethics is a moral principle and action that becomes the basis of one's actions so that what he does is viewed by society as a commendable deed and enhances one's dignity and honor. Ethics is closely related to moral behavior. Professional ethics is a field of special or applied ethics which is the product of social ethics. The heart of ordinary intentions is also called karsa or will, will. And the content of this initiative will be realized by deeds.The legal obligation of a publik accountant is responsible for every aspect of his / her duties so that if an error occurs as a result of the auditor's negligence, then the publik accountant may be held accountable by law as a form of auditor's legal obligation.The auditor's legal responsibilities are heavier, but this is not a cue to panic. The auditor shall be solely responsible for the opinion of the financial statements and that opinion shall have the weight of integrity and professional competence based on established standards. So legal liability is not a threat to auditors but rather a challenge to work more professionally and independently. The need for a definitive legal tool for organizing publik accountants in Indonesia to complement existing rules of the game.